Immediate outcome prognostic value of plasma factors in patients with acute ischemic stroke after intravenous thrombolytic treatment - Lu, Huanhuan; Li, Siyi; Zhong, Xin; Huang, Shuxuan; Jiao, Xue; He, Guoyong; Jiang, Bingjian; Liu, Yuping; Gao, Zhili; Wei, Jinhong; Lin, Yushen; Chen, Zhi; et al. (BMC neurology, 2022)
In the present study, we explored multiple plasma factors to predict the outcomes of patients with AIS after IVT. Fifty AIS patients who received IVT with alteplase were recruited and divided into two groups according to their NIHSS scores. Serum from all subjects was collected to quantitatively analyze the levels of different plasma factors, IL-6, MMP-9, ADAMTS13, TNC, GSN and TRX, using Luminex assays or ELISA measurements. Compared with the levels assessed at the onset of AIS, the levels of MMP-9 ( P < 0.001), ADAMTS13 ( P < 0.001), and TRX ( P < 0.001) significantly decreased after IVT. The level of IL-6 was significantly increased in the NIHSS > 5 group at admission ( P < 0.001) compared to the NIHSS ≤ 5 group. AIS patients with a poor prognosis had lower levels of ADAMTS13 at 72 h post-IVT compared with patients with a good prognosis ( P = 0.021). IL-6 also was notably higher in the poor outcome group ( P = 0.012). After adjusting for confounders, ADAMTS13 at 72 h post-IVT was an independent protective factor for prognosis in AIS patients with an adjusted OR of 0.07 ( P = 0.049), whereas IL-6 was an independent predictor of risk for AIS patients with an adjusted OR of 1.152 ( P = 0.028). IVT decreased MMP-9, ADAMTS13, and TRX levels in the plasma of AIS patients. Patients with a NIHSS score of less than 5 exhibited lower IL-6 levels, indicating that increased levels of IL-6 correlated with AIS severity after IVT. Therefore, IL-6 and ADAMTS13 might be useful plasma markers to predict the prognosis in AIS patients at 90-days after IVT.